2018
DOI: 10.1016/j.clnu.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Redefining essential fatty acids in the era of novel intravenous lipid emulsions

Abstract: The essentiality of fatty acids was determined by the Burrs in the 1920s. Subsequently, it is commonly accepted that provision of linoleic (LA) and alpha-linolenic acids (ALA) prevents and reverses essential fatty acid deficiency (EFAD). Development of alternative injectable lipid emulsions (ILE) low in LA and ALA has raised concern about their ability to prevent EFAD. This review provides biochemical evidence coupled with observations from animal and human studies that aim to characterize which fatty acids ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 63 publications
0
56
0
1
Order By: Relevance
“…To prevent EFAD, a minimum linoleic acid of 0.25 g/kg/day in preterm infants and 0.1 g/kg/day in term infants and older children is recommended . It has been reported that in an era of lipid restriction and alternative IV lipid emulsion strategies, providing adequate doses of ARA and docosahexaenoic acid can prevent EFAD by retroconversion and mobilization of EFAs (linoleic acid and α‐linolenic acid, respectively) from tissues . When the CLE dose is restricted in infants with minimal or no enteral intake, EFAD can occur as noted in infants 1 and 2 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent EFAD, a minimum linoleic acid of 0.25 g/kg/day in preterm infants and 0.1 g/kg/day in term infants and older children is recommended . It has been reported that in an era of lipid restriction and alternative IV lipid emulsion strategies, providing adequate doses of ARA and docosahexaenoic acid can prevent EFAD by retroconversion and mobilization of EFAs (linoleic acid and α‐linolenic acid, respectively) from tissues . When the CLE dose is restricted in infants with minimal or no enteral intake, EFAD can occur as noted in infants 1 and 2 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…12 It has been reported that in an era of lipid restriction and alternative IV lipid emulsion strategies, providing adequate doses of ARA and docosahexaenoic acid can prevent EFAD by retroconversion and mobilization of EFAs (linoleic acid and α-linolenic acid, respectively) from tissues. 13 When the CLE dose is restricted in infants with minimal or no enteral intake, EFAD can occur as noted in infants 1 and 2 (Figure 1). Since this CLE contains only 30% soybean oil, a minimum dose of 2.5 g/kg/day (equivalent to 0.83 g/kg/day SOLE) may be required to prevent EFAD as observed in case 3 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of the new‐generation lipid emulsions (SMOFlipid and Omegaven), vitamin E provision in PN has considerably changed. The vitamin E content of Intralipid and Clinoleic is, respectively, 13 mg/L and 30 mg/L compared to approximately 200 mg/L in SMOFlipid and Omegaven (Table ) . This has resulted in an increase in vitamin E levels, a potent antioxidant, with better liver protection and other beneficial effects .…”
Section: Long‐term Laboratory Monitoringmentioning
confidence: 99%
“…Historically, EFAs have been considered LA, the primary precursor of the ω‐6 fatty acid family, and α‐linolenic acid (ALA), the main precursor of the ω‐3 fatty acid family. Recent evidence, however, has questioned the true essentiality of LA and ALA, since their main downstream products, arachidonic acid (ARA) and DHA, respectively, seem just as effective at preventing an EFAD and promoting growth …”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the underlying disease, patients receiving PN are at risk for developing an iatrogenic EFAD in the setting of inadequate or inadequately balanced ILE provision. Traditionally, it was believed that a minimum of 1% of total calories from LA and between 0.2% and 0.5% from ALA were required to prevent an EFAD, and higher percentages of LA an ALA may be required for certain patients such as premature infants and those with extensive inflammation . Because fish oil ILE contains a small amount of LA and ALA, many people postulated that fish oil ILE monotherapy would cause an EFAD.…”
Section: Introductionmentioning
confidence: 99%